Bidirectional mechanisms and emerging strategies for implantable bioelectronic interfaces - Zineng Yan; Weihang Gao; Yuyu Duan; Hong Zhou; Changmao Ni; Li Huang; Zhewei Ye (Bioactive Materials)
Neural network functionality depends on the signaling of excitable cells and intricate synaptic connections, which collectively promote advanced functions of the brain, such as perception, motor control, and cognition. Neurological diseases may cause changes in the structure and connection patterns of neural networks, thereby leading to loss of motor and sensory functions. Neural interfaces are dependable tools for recording or stimulating neural circuit dynamics, but conventional neural implants do not align with the physicochemical characteristics of living tissues, resulting in eventual failure of these interface devices. These challenges in neuroengineering have spurred progress in materials science. In this account, we explore the interaction mechanisms between electrodes and biological tissues, offering strategies to meet the electrochemical and biocompatibility demands of bioelectronic interfaces in engineering, with an emphasis on the structural design and manufacturing technologies of implantable devices.